Conceptualizations and instructional strategies on critical thinking in higher education: A systematic review of systematic reviews - Andreucci-Annunziata, Paola; Riedemann, Andrea; Cortés, Susana; Mellado, Augusto; del Río, María Teresa; Vega-Muñoz, Alejandro (Frontiers in Education, 2023)
This systematic review identified systematic reviews encompassing quantitative and qualitative empirical studies on the fostering and development of critical thinking in higher education students that allowed us to answer the following research questions: (1) What are the main definitions of critical thinking found in systematic reviews on critical thinking in higher education, and which are their commonalities and differences? and (2) Which are the most frequently used instructional strategies in HE for teaching or encouraging critical thinking, and how effective have they proven to be? Methods: The systematic reviews were selected according to the Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and the eligibility criteria proposed by the PICOS strategy (population, interventions, comparators, outcomes, and study design) based on 23 records of scientifically identified registers in the Journal Citation Report databases of the Web of Science. Results: The bibliometric and systematic review of reviews of empirical studies on the topic allowed the selection of five systematic reviews. The results highlighted that conceptually critical thinking is related both to dispositions and to skills and that although there is no consensus on its definition, it is established that it is a higher-order cognitive process that can be trained. However, the results show that more studies have been conducted considering critical thinking as a skill than as a disposition, that the immersion approach has been widely used, and that some instructional strategies have shown greater effectiveness than others if the disciplines are evaluated independently. Discussion: This review highlights the difficulties of critical thinking conceptualization, some issues of the relation between dispositions and skills, and its assessment in academic fields, despite the relative consensus on its importance for professional development in higher education.